RATIO DECIDENDI PENGADILAN TATA USAHA NEGARA TERHADAP PERKARA PEMBERHENTIAN PEGAWAI NEGERI SIPIL: STUDI PUTUSAN NOMOR 26/G/2016/PTUN.PLK DAN PUTUSAN NOMOR 19/G/2019PTUN.PLK - Wibawa, Arga Andhika Putra; Octarina, Nynda Fatmawati (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The dismissal of civil servants can occur due to criminal acts committed due to criminal crime or crimes that have to do with their positions. But what happened was the judge's consideration practice, there was also a dismissal that reaped the controversy after the lawsuit in the administrative court was rejected as happened in the case of the decision number 19/G/2019/PTUN.PLK. As this case there there was a dispute between Piri Ahadi against Sukamara Regent with a lawsuit of dispute objects against Sukamara Regent Decree Number 888/50/BKD while in the previous case that occurred in the decision Number 26/G/PTUN.PLK with the object of the Sukamara Regent Decree Number 888/11/BKPP was found by the cancellation of the Decree and this was the main problem that arose in this study. First, the PTUN decision analysis in decision number 26/G/2016/PTUN.PLK and 19/G/2019/PTUN.Plk. Second, the analysis of judges' considerations between decision number 26/G/2016/PTUN.PLK and Decision Number 19/G/2019/PTUN.PLK This study uses the legislation approach method, conceptual approach, and case study approach